Prevalences of aflatoxin (AFM1) in raw milk: A review - Sadam S. M. Y.; Malaka R.; Baco S.; Mustabi J.; Waqiah S. N. (BIO Web of Conferences)
Dairy and dairy products are particularly susceptible to AFM1 contamination, which is thought to pose a number of health risks to consumers. As a result, dairy and dairy products have the most clearly shown potential for the human diet to contain aflatoxin residues. Children, particularly infants, may be more vulnerable and sensitive to AFM1 exposure than adults, and their capacity for carcinogen biotransformation is slower than grownups. The severity of AFM1 in dairy can be significantly reduced by implementing outsourced control strategies like providing livestock with high-quality feed. Onsite monitoring of the occurrence of AFM1 throughout the raw milk supply chain, from the udder of the cow to the factory and to the consumer, is warranted. Likewise, the good control condition framework for AFB1 rations defilement is critical to significant in the event of the nation considering the environmental change situations. There have been some investigations of milk's AFM1 content. Still, the current focus must be creating an effective and sensitive method for determining its presence in dairy and dairy products. This review aimed to assess and review the prevalence of aflatoxin M1 in human-useable raw milk and its potential obstacles in the future food and rations formulations companies.